2012
DOI: 10.1111/j.1365-2850.2012.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

Do mental health professionals enquire about childhood sexual abuse during routine mental health assessment in acute mental health settings? A substantive literature review

Abstract: This literature review examines the extent to which mental health professionals enquire about childhood sexual abuse during routine mental health assessments in acute mental health settings. Five electronic databases were searched for papers which explored the nature of enquiry about childhood sexual abuse by mental health professionals. The literature was searched between December 2008 and March 2010, with an update in October 2011. Of the 332 papers identified, 54 papers were selected as potentially relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 37 publications
2
60
0
1
Order By: Relevance
“…Despite guidelines emphasising the need to routinely assess adversity exposure in psychiatric serviceusers (National Health Service Confederation, 2008), research suggests such recommendations are often not implemented (Read et al 2007;Fisher et al 2011;Hepworth & McGowan, 2013).While staff should not pre-suppose a history of maltreatment unless confirmed by the client, the current findings support the contention that clinicians should receive support and training for making routine evaluations for possible experiences of maltreatment. This is particularly important given the significant under-detection of posttraumatic stress in patients diagnosed with psychosis (Salyers et al 2004;Lommen & Restifo, 2009;Mauritz et al 2013), and that such individuals are less likely to receive an appropriate clinical response (e.g., trauma-focused interventions) relative to those with non-psychotic diagnoses (Agar & Read, 2002;Salyers et al 2004;Grubaugh et al 2011) especially in instances where healthcare workers have strong convictions about biogenetic aetiology (Read & Fraser, 1998;Young et al 2001;Agar & Read, 2002).…”
Section: Discussionsupporting
confidence: 63%
“…Despite guidelines emphasising the need to routinely assess adversity exposure in psychiatric serviceusers (National Health Service Confederation, 2008), research suggests such recommendations are often not implemented (Read et al 2007;Fisher et al 2011;Hepworth & McGowan, 2013).While staff should not pre-suppose a history of maltreatment unless confirmed by the client, the current findings support the contention that clinicians should receive support and training for making routine evaluations for possible experiences of maltreatment. This is particularly important given the significant under-detection of posttraumatic stress in patients diagnosed with psychosis (Salyers et al 2004;Lommen & Restifo, 2009;Mauritz et al 2013), and that such individuals are less likely to receive an appropriate clinical response (e.g., trauma-focused interventions) relative to those with non-psychotic diagnoses (Agar & Read, 2002;Salyers et al 2004;Grubaugh et al 2011) especially in instances where healthcare workers have strong convictions about biogenetic aetiology (Read & Fraser, 1998;Young et al 2001;Agar & Read, 2002).…”
Section: Discussionsupporting
confidence: 63%
“…Despite guidelines emphasizing the need to routinely assess adversity exposure in psychiatric service-users (National Health Service Confederation [NHS], 2008), such recommendations are not always adequately implemented (Hepworth and McGowan, 2013). While a history of maltreatment should not be presupposed, the evidence outlined here supports the contention that clinicians should receive adequate support and training for making routine enquiries about abuse and adversity.…”
Section: Therapeutic Implicationsmentioning
confidence: 91%
“…Clearly, the impact of such traumatic events as physical, psychological, and sexual abuse in childhood and later in adulthood is directly related to women's health issues (Al-Modallal, Abuidhail, Sowan, & Al-Rawashdeh, 2010;Amar & Alexy, 2005;Chouliara et al, 2013;Hepworth & McGowan, 2012;Paranjape, Sprauve-Holmes, Gaughan, & Kaslow, 2009;Pigeon et al, 2011;Sigurdardottir & Halldorsdottir, 2013;Svavarsdottir & Orlygsdottir, 2008). Pico-Alfonso and colleagues (2006) found that when compared to women who were not victims of IPV, women who were exposed to physical and psychological abuse, or to psychological abuse only, had a noticeably increased level of severe depression and anxiety symptoms; this included the possible development of posttraumatic stress disorder (PTSD) as well as suicidal thoughts and attempts.…”
mentioning
confidence: 97%